„Niecodzienna codzienność”. Świat społeczny osób z chorobą Parkinsona - Szluz, Beata; Jamrógiewicz, Beata (Uniwersytet Marii Curie-Skłodowskiej w Lublinie, 2024)
Choroba Parkinsona jest jedną z najczęstszych chorób neurozwyrodnieniowych. Podstawowymi objawami choroby Parkinsona są bradykinezja, drżenie i sztywność plastyczna. Społeczne badania naukowe nad doświadczaniem chorób przewlekłych koncentrują się bezpośrednio na kluczowych graczach w służbie zdrowia – ludziach chorych. Badacze zdrowia, praktycy i decydenci mogą twierdzić, że reprezentują obawy pacjentów, rzadko jednak uwypuklają opinie na temat doświadczenia pacjentów w zakresie opieki zdrowotnej, a tym bardziej w odniesieniu do tego, co oznacza życie z chorobą przewlekłą. Celem badań było rozpoznanie i przedstawienie ich społecznego świata na podstawie narracji będącej subiektywną rekonstrukcją ich historii życia. Do badań wykorzystano autobiograficzny wywiad narracyjny zaproponowany przez Schützego, który opracował metodę jako spójną koncepcję badań biograficznych. Zebrany materiał empiryczny (44 wywiady) został poddany analizie, co umożliwiło udzielenie odpowiedzi na postawione pytania i sformułowanie wniosków, to zaś pozwoliło na wzbogacenie posiadanej wiedzy o jakościowy aspekt analizy. Badania nad chorobą przewlekłą ukazują, jak ludzie postrzegają siebie jako osoby przewlekle chore i jak choroba wpływa na ich życie.

Parkinson’s disease is one of the most frequent neurodegenerative disorders. The core symptoms of Parkinson’s disease are bradykinesia, tremor and plastic rigidity. Social scientific research on experiencing chronic illness focuses directly on pivotal players in health care – people who are sick. Health researchers, practitioners and policy makers may claim to represent patients’ concerns. However, they seldom obtain systematic “in-depth” views of patients’ experience of health care, much less of what it means to live with continued illness. The aim of the study was to recognize and present their social world on the basis of a narrative which is a subjective reconstruction of their life history. The technique of an autobiographical narrative interview was used for the research, as proposed by Schütz, who developed the method as a cohesive concept of biographical research. The collected empirical material (44 interviews) was analyzed, providing answers to the posed questions and allowing the formulation of conclusions, which made it possible to enrich the existing knowledge with the qualitative aspect of the analysis. The research on experiencing chronic illness emphasizes how people come to view themselves as chronically ill and how illness affects their lives.
“Unusual Everyday Life”: The Social World of People with Parkinson’s Disease
Keywords: choroba Parkinsona; świat społeczny; badania biograficzne; choroba przewlekła; Parkinson's disease; social world; biographical research; chronic illness